Digital Marketing Tips on Instagram (Case Study on Madu Modow Honey SME) - Elvi Lastriani; Mira Rosmala; David Opel Alexander; Muhammad Hafiz Abd Rashid; Amiral Arief Absy; Dian Syah Putri (Eastasouth Institute, 2025)
This Community Service (PKM) activity was conducted by STIE Dharma Putra at the Madu Madow Honey MSME in Siak Regency, Riau, in June 2025. This MSME produces premium-quality Sialang Siak Honey but faces challenges in digital marketing and preparing simple financial reports. The activity's title was